(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Cakes produced from composite flour were investigated for proximate and sensory qualities. The attributes were developed and evaluated by using standard laboratory procedures. The composite flour was prepared with using Finger millet flour, Soya flour, oats flour & refined wheat flour. Five different varieties of cakes were prepared. Refined wheat flour to composite flour proportion in preparation of cakes were as follows: A 0 (100%:0), A 1 (80%:20% ) , A 2 (60%:40%) , A3 (40%:60%) and A 4 (20%:80%) .The data generated were analyzed statistically by one way analysis of variance (ANOVA). Theproximate composition for the developed cakes were shown an increase in energy value(387.68–397.50 kcal/100 g), protein (6.20-14.30%),ash content from (1.41–2.98%), fat (12.95–16.51%), crude fibre (1.08–4.77%) as well as decrease in moisture (16.78–13.51%) & carbohydrate content (61.59–47.92%). The above results indicated that as the substitution level of flour mixture increases, there will be increase in protein, fat, fiber & ash percentage and decrease in carbohydrate and moisture percentage. The sensory test was conducted by using 9- point hedonic scale rating for acceptance of the developed products. These results found that the cakes varied in appearance (8.2-6.6), colour (8.0–6.1), taste (8.4–6.6), flavour (8.8–7.0), texture (8.4–6.4) and overall acceptability (6.46–8.34). The control sample had the highest sensory scores for colour than all other attributes. The proximate composition values for protein, fat, ash, fiber and energy content increased as the composite flour quantity increases but on the basis of the sensory evaluation, at 40% incorporation of composite flour, the developed cake(A2) is most acceptable in comparison to others. In conclusion, the developed cakes made with composite flour substitution are well accepted and also are rich in both micro and macronutrient. Hence it could make a significant contribution for the consumers as well as bakery industry.